The contribution of female health to economic development - David E. Bloom; Michael Kuhn; Klaus Prettner (Vienna University of Technology, Institute of Statistics and Mathematical Methods in Economics, Research Group Economics, 2015)
We analyze the economic consequences for less developed countries of investing in female health. In so doing we introduce a novel micro-founded dynamic general equilibrium framework in which parents trade off the number of children against investments in their education and in which we allow for health-related gender differences in productivity. We show that better female health speeds up the demographic transition and thereby the take-off toward sustained economic growth. By contrast, male health improvements delay the transition and the take-off because ceteris paribus they raise fertility. According to our results, investing in female health is therefore an important lever for development policies. However, and without having to assume anti-female bias, we also show that households prefer male health improvements over female health improvements because they imply a larger static utility gain. This highlights the existence of a dynamic trade-off between the short-run interests of households and long-run development goals. Our numerical analysis shows that even small changes in female health can have a strong impact on the transition process to a higher income level in the long run. Our results are robust with regard to a number of extensions, most notably endogenous investment in health care.
Keywords: O11; I15; I25; J13; J16; 330; economic development; educational transition; female health; fertility transition; quality-quantity trade-off